The political influence of the Borgias in the thought of Niccolo Maquiavelli - Torre Gannown, Guido José (2018)
In the following investigation an interpretation will be developed of the political concept established in the thought of Machiavelli. The following paper suggests determining, through the study of the lives and political exercise of Rodrigo and César Borgia, how and to what extent these 16th-century Italian characters influenced the development of the political thought of the Florentine which are reflected in his book The Prince. In order to achieve the above, it starts from an analysis of the comparative historical method implemented by Machiavelli in his text The Prince, for which has it been affirmed that he holds the title of father of political science.